Chapter Аспектуальные антиномии в русском языке (на славянском фоне) - Petruchina, Elena V. (Biblioteca di Studi Slavistici, 2017)
This article discusses some antinomies concerning the category of verbal aspect in Russian, which generate apparent contradictions on a theoretical level. Special attention is paid to Russian aspectual pairs (considered in a cross-Slavic perspective). I focus on antinomies applying to different ways of expressing the aspectual semantics of verbs (lexical, grammatical and derivational), as well as on rules regulating the use of perfective and imperfective verbs. Our study confirms the need to distinguish between lexical and grammatical limits of action in a theory of Slavic aspect.